A model system for cell adhesion and signal transduction in Drosophila. - Peifer, M.; Orsulic, S.; Pai, L.M.; Lourerio, J. (Development - Supplement, 1993)
Cells must cooperate and communicate to form a multicellular animal. Information about the molecules required for these processes have come from a variety of sources; the convergence between the studies of particular molecules by vertebrate cell biologists and the genes identified by scientists investigating development in Drosophila has been especially fruitful. We are interested in the connection between cadherin proteins that regulate cell-cell adhesion and the wingless/wnt-1 cell-cell signaling molecules controlling pattern formation during development. The Drosophila segment polarity gene armadillo, homolog of the vertebrate adherens junction protein beta-catenin, is required for both cell adhesion and wg signaling. We review what is known about wingless signaling in Drosophila, and discuss the role of cell-cell junctions in both cell adhesion and cell communication. We then describe the results of our preliminary structure-function analysis of Armadillo protein in both cell adhesion and wingless signaling. Finally, we discuss evidence supporting a direct role for Armadillo and adherens junction in transduction of wingless signal.